The incidence of type 2 diabetes in patients presenting for bariatric metabolic surgery at a tertiary bariatric surgery centre in India - Bhandari, Mahak; Bhandari, Mohit; Mathur, Winnie; Behl, Simran; Kosta, Susmit (International Journal of Research in Medical Sciences, 2018)
Background: In recent years, there has been a marked change in life-style of developing countries caused by economic growth, affluence, urbanization and dietary westernization. Few studies on the prevalence of obesity with diabetes in the Indian population have been reported. Therefore, this study was planned to estimate the prevalence of type 2 diabetes (T2D) in patients presenting for at a tertiary bariatric surgery centre in India. Methods: In this retrospective study, authors estimated the prevalence of T2D by analyzing the hospital-based data, who were came for bariatric surgery at tertiary bariatric surgery centre in India from January 2010 to June 2018. Results: From the hospital-based data of eight years the incidence of T2D was found 24% of the Indian population in series, who came for bariatric metabolic surgery (BMS). There was slight male preponderance in incidence of T2D based on gender. The higher incidence of T2D was found mostly in 45-60 years age group in both the male and female patients. Incidence of T2D in class of obesity was 4.3% of class I, 18.6% of class II and 77.1% in class III. The incidence of hypertension was seen 41.8% and co-prevalence of both obstructive sleep apnea syndrome and hypertension was 16.2%. Conclusions: Age and higher BMI are strongly and independently associated with the risk of being diagnosed with T2D. The association of BMI class on the risk of T2D is stronger for people with a higher BMI relative to people with a lower BMI.